Plantas entre los juruna: en busca de una metodología para el estudio del léxico - Fargetti, Cristina Martins [UNESP] (My University, 2012)
This paper presents methodological considerations related to the study of the plant lexicon of the Juruna ethnic group, an indigenous people of the Xingu Indigenous Park, Mato Grosso State, Brazil. The language of this ethnic group, along with that spoken by the Xipaya, belongs to the Juruna family of the Tupi stock. It is a tonal language with SOV syntactic structure (Fargetti 1992, 2007), and presents interesting processes of reduplication (Fargetti 1997). Part of our broader research project on the lexicology and lexicography of the language, research on the Juruna plant lexicon is still in development, together with studies of other semantic fields such as birds, material culture, and kinship relations. However, it is already possible to see interesting linguistic issues involving word formation, as well as issues of the relationship between language and culture (especially those related to “perspectivism”). These issues are presented in this paper.

Este trabajo presenta algunas consideraciones metodológicas relacionadas al estudio del léxico de plantas entre los juruna, un pueblo indígena del Parque Xingú, Estado de Mato Grosso, Brasil. La lengua de esta etnia, junto con aquélla hablada por los xipaya, pertenece al tronco tupí, familia juruna. Es una lengua tonal, de estructura sintáctica SOV (Fargetti 1992, 2007) y que presenta procesos interesantes de reduplicación (Fargetti 1997). Inserida en nuestro proyecto de estudio más amplio en torno a la lexicología y lexicografía de la lengua, esta investigación se encuentra aún en desarrollo, juntamente con estudios de otros campos semánticos, tales como aves, cultura material, relaciones de parentesco. Sin embargo, ya es posible observar cuestiones lingüísticas de interés que envuelven la formación de palabras, y cuestiones de relación entre lengua y cultura, especialmente el “perspectivismo”, que son también presentadas en este trabajo .
Keywords: Plants; Juruna; Word formation; Lexicon; Etnobotânica; Lexicologia; Língua Juruna